Some results of studies on leaching of toxic elements in Asgat polymetallic concentrate (Bulletin of the Institute of Chemistry and Chemical Technology, 2021)
Extended ICP-OES and AAS analysis of floated polysulphide concentrate from the Asgat polymetallic ore revealed that the concentrate contains 0.91% of silver, 18.2% of copper, 19.4% antimony, 2.03% arsenic and 1.6% of bismuth together with other elements. The prevailing minerals in the concentrate are tetrahedrite, bismuthinite, chalcopyrite, arsenopyrite and pyrite and non-ore minerals i.e. siderite, muscovite and quartz. The content of above minerals was estimated by the X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) analysis. An optimum condition for antimony leaching from the tetrahedrite by alkaline-sulphide solution was studied comprehensively. In optimized condition, the 99.25% of Sb, 89.0% of As and 44.50% of Bi were dissolved from the concentrate into the alkaline-sulphide solution, successfully. The solid residue contains non-ore sulphide minerals as well as chalcopyrite (CuFeS2), covellite (CuS), chalcocite (Cu2S), pyrite (FeS) and argentite (Ag2S). Chalcopyrite and pyrite are not soluble in alkaline-sulphide solution. The covellite and chalcocite are the product of tetrahedrite decomposition. The activation energy for antimony leaching from the tetrahedrite by alkaline-sulphide solution was calculated as 81.43kJ/mol that indicates the leaching process occurred by chemical reaction. Асгатын полиметаллын баяжмал дахь хортой элементүүдийг уусгах аргаар ялгаж авах судалгааны зарим үр дүнХураангуй: Асгатын полиметаллын хүдрийг флотацийн аргаар баяжуулан гаргаж авсан полисульфидын баяжмалд 0.91% мөнгө, 19.20% зэс, 19.40% сурьма, 2.03% хүнцэл, 1.60% висмут болон бусад дагалдах элемент агуулагдаж байгааг атом шингээлтийн (AAS) болон индукцийн холбоот плазмын спектроскоп (ICP-OES)-ын аргуудаар тодорхойлсон. Баяжмалын эрдэс бүрдлийн найрлагыг рентгендифрактометр (XRD), электрон микроскоп, энергийн сарнилын спектрометр (SEM-EDS)-ийн аргуудаар тодорхойлоход тетраэдрит, висмутин, халькопирит, арсенопирит, пирит зэрэг үндсэн эрдсүүдээс гадна сидерит, мусковит, кварц зэрэг хүдрийн бус эрдсүүд агуулагдаж байв. Баяжмалыг шүлт-сульфидын (Na2S+NaOH) холимогт уусгаж, хортой бүрдэл болох сурьмаг уусгах аргаар ялгаж авах тохиромжтой нөхцлийг туршилтаар тогтоов. Тохиромжтой нөхцөлд баяжмалаас шүлт-сульфидын уусмалд сурьма 99.25%, хүнцэл 89.00%, висмут 44.50% ууссан. Уусгалтын хатуу үлдэгдэлд хүдрийн бус эрдсүүд болон халькопирит (CuFeS2), ковелин (CuS), халькозин (Cu2S), пирит (FeS2), аргентит (Ag2S) зэрэг сульфидын эрдсүүд илэрсэн. Шүлт-сульфидын холимогт халькопирит, пирит уусахгүй. Ковелин, халькозин нь тетраэдритийн задралаар үүссэн. Тетраэдритээс сурьмаг шүлт-сульфидын холимогоор уусгах урвалын идэвхжилийн энергийг тооцоолоход 81.43 кЖ/моль байгаа нь уг процесс химийн урвалаар явагдсан болохыг харуулж байна.Түлхүүр үг: полисульфидын баяжмал, тетраэдрит, идэвхжилийн энерги.